Geographic Distribution of Ammonia-Oxidizing Archaea along the Kuril Islands in the Western Subarctic Pacific - Jing, Hongmei; Cheung, Shunyan; Xia, xiaomin; Suzuki, Koji; Nishioka, Jun; Liu, Hongbin (Frontiers in Microbiology, 2017)
Community composition and abundance of ammonia-oxidizing archaea (AOA) in the ocean were affected by different physicochemical conditions, but their responses to physical barriers (such as a chain of islands) were largely unknown. In our study, geographic distribution of the AOA from the surface photic zone to the deep bathypelagic waters in the western subarctic Pacific adjacent to the Kuril Islands was investigated using pyrosequencing based on the ammonia monooxygenase subunit A (amoA) gene. Genotypes of clusters A and B dominated in the upper euphotic zone and the deep waters, respectively. Quantitative PCR assays revealed that the occurrence and ammonia-oxidizing activity of ammonia-oxidizing archaea (AOA) reached their maxima at the depth of 200 m, where a higher diversity and abundance of actively transcribed AOA was observed at the station located in the marginal sea exposed to more terrestrial input. Similar community composition of AOA observed at the two stations adjacent to the Kuril Islands maybe due to water exchange across the Bussol Strait. They distinct from the station located in the western subarctic gyre, where sub-cluster WCAII had a specific distribution in the surface water, and this sub-cluster seemed having a confined distribution in the western Pacific. Habitat-specific groupings of different WCB sub-clusters were observed reflecting the isolated microevolution existed in cluster WCB. The effect of the Kuril Islands on the phylogenetic composition of AOA between the Sea of Okhotsk and the western subarctic Pacific is not obvious, possibly because our sampling stations are near to the Bussol Strait, the main gateway through which water is exchanged between the Sea of Okhotsk and the Pacific. The vertical and horizontal distribution patterns of AOA communities among stations along the Kuril Islands were essentially determined by the in situ prevailing physicochemical gradients along the two dimensions.